USE OF HERBS FOR TREATMENT OF DIABETES MELLITUS - Nagiyeva, Mahruh Mahmud; Mammadova, Aytakin Sabuhi; Tagizade, Aybaniz Turkan; Aliyev, Oktay Veli; Kazimzade, Huseyn Ceyhun (Eastern Ukrainian Medical Journal, 2025)
Introduction: Medicinal plants have been widely used in traditional medicine for their potential in managing diabetes mellitus by regulating blood sugar levels and improving overall metabolic health. As diabetes mellitus continues to be a global health problem, natural remedies derived from plants have attracted attention for their efficacy and fewer side effects compared to synthetic medicines. Many cultures traditionally rely on herbal remedies to treat diabetes-related symptoms, and modern research continues to validate these traditional practices. Methods: The antidiabetic properties of medicinal plants are mainly attributed to their bioactive compounds, which include flavonoids, alkaloids, terpenoids, polyphenols and saponins. These substances contribute to blood sugar regulation through various mechanisms. Some plants increase insulin secretion from pancreatic beta cells, while others increase insulin sensitivity in peripheral tissues such as muscle and liver. Some medicinal plants prevent spikes in blood sugar by slowing the digestion and absorption of carbohydrates in the intestines. Moreover, some plants have antioxidant and anti-inflammatory properties, protecting pancreatic cells from damage and supporting their function. Results: Scientific studies have shown that several medicinal plants effectively lower fasting blood glucose levels, improve glucose uptake by cells and reduce long-term glucose markers such as HbA1c. Some plants also contain soluble fibre that slows glucose absorption and improves glycaemic control. Moreover, some herbs have been shown to reduce inflammation, oxidative stress and insulin resistance, which are important factors in the progression of diabetes mellitus. Conclusions: Although medicinal plants offer important benefits in the treatment of diabetes mellitus, their proper use, dosage and preparation methods should be carefully monitored. Possible interactions with conventional antidiabetic drugs should be taken into account and people should consult their doctor before incorporating herbal therapies into their routine.